74.0k views
0 votes
Evaluate the expression, if x = 5 and y = 3. x + y = 1*

Evaluate the expression,
if x = 5 and y = 3.
x + y - 1

Evaluate the expression, if x = 5 and y = 3. x + y = 1* Evaluate the expression, if-example-1
User Regomodo
by
7.3k points

2 Answers

3 votes

Answer:

7

Explanation:

If you plug in the variable for x and y you get:

5+3-1

Use the order of operations to solve:

5+3-1

8-1

7

User Waleed Tariq
by
7.0k points
4 votes

Substituting x = 5 and y = 3 into x + y - 1 results in 7, illustrating a basic application of arithmetic operations after the values are substituted.

To evaluate the expression x + y - 1 with x = 5 and y = 3, substitute these values into the equation:

x + y - 1 = 5 + 3 - 1

Performing the arithmetic operations, we get:

x + y - 1 = 8 - 1 = 7

Therefore, when x is assigned the value of 5 and y is assigned the value of 3, the result of the expression x + y - 1 is 7. This process involves substituting the given values into the variables within the expression and performing the subsequent mathematical operations.

In summary, when x is 5 and y is 3, the expression x + y - 1 evaluates to 7, showcasing a straightforward application of substitution and arithmetic operations with the added subtraction of 1.

User Rajendran Nadar
by
7.2k points